Poetic operations : trans of color art in digital media - cárdenas, micha, 1977- (Asterisk (Duke University Press), 2022)
"Artist and theorist micha cárdenas considers contemporary digital media, artwork, and poetry in order to articulate trans of color strategies of safety and survival."--